Multimodal Composing in Special Education: A Review of the Literature. Issue 2 (June 2013) - Bruce, David; Di Cesare, Dane Marco; Kaczorowski, Tara; Hashey, Andrew; Boyd, Emily Hoeh; Mixon, Toni; Sullivan, Melissa
Focus on multimodal learning, especially composition, is increasing in K–12 classrooms, particularly among those whose populations are struggling academically. This shift toward multimodal learning also is evident in special education classrooms. This review explored multimodality and its impact on the composition practices of students with disabilities. Eleven empirical studies discussing research designs, research questions, and various sample characteristics were included. Themes from the findings and implications included the role of technology in instruction, its use in providing scaffolds, and its impact on student success. Additionally, several nonempirical articles advocating the use of multimodal composition were addressed. This review concludes with implications for teachers and researchers, focusing on the benefits of multimodal composition, particularly the underexplored area of digital video (DV) composition, for students with disabilities.